Development of Bioaffinity Chromatography for Uricase Purification - Salleh, Abu Bakar (1980)
The uricase inhibitors urate, xanthine, oxonate and cyanurate were tried as ligands, for preparing bioaffinity support for chromatographic separation of uricase. Only derivatised purines showed inhibitory properties, whereas derivatised s-triazines seemed to lose their absorptive capacity. Chromatographic separation on a bioaffinity support produced higher yield and better purification of Uricase than conventional chromatographic technique.